2017
DOI: 10.1186/s11671-017-2130-9
|View full text |Cite
|
Sign up to set email alerts
|

One-step electrospinning route of SrTiO3-modified Rutile TiO2nanofibers and its photocatalytic properties

Abstract: The SrTiO3 modified rutile TiO2 composite nanofibers were synthesized by a simple electrospinning technique. The result of XRD, SEM and TEM indicate that the SrTiO3/TiO2 heterojuction has been prepared successfully. Compared with the TiO2 and SrTiO3, the photocatalytic activity of the SrTiO3/TiO2 (rutile) for the degradation of methyl orange exhibits an obvious enhancement under UV illumination. which is almost 2 times than that of bare TiO2 (rutile) nanofiber. Further, the high crystallinity and photon-genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Motivated by the efficient charge separation, researchers have developed a large number of traditional type‐II heterojunctions where electrospun TiO 2 NFs were composed of various semiconductors including metal oxides, [ 73,108–117 ] metal sulfides, [ 118–121 ] halides, [ 122 ] and so on. [ 123–127 ] For instance, Zhang et al [ 119 ] fabricated 1D In 2 S 3 /TiO 2 hierarchical NFs by combining the electrospinning technique (for TiO 2 NFs) with the hydrothermal method (for In 2 S 3 nanosheets). They found that such In 2 S 3 /TiO 2 composite NFs exhibited promising charge separation efficiency and high visible light photocatalytic activity for degradation of methyl orange and reduction of Cr (VI) under visible light illumination due to the formation of the traditional type‐II heterojunction between In 2 S 3 nanosheets and TiO 2 NFs ( Figure a).…”
Section: Electrospun Tio2 Nfsmentioning
confidence: 99%
“…Motivated by the efficient charge separation, researchers have developed a large number of traditional type‐II heterojunctions where electrospun TiO 2 NFs were composed of various semiconductors including metal oxides, [ 73,108–117 ] metal sulfides, [ 118–121 ] halides, [ 122 ] and so on. [ 123–127 ] For instance, Zhang et al [ 119 ] fabricated 1D In 2 S 3 /TiO 2 hierarchical NFs by combining the electrospinning technique (for TiO 2 NFs) with the hydrothermal method (for In 2 S 3 nanosheets). They found that such In 2 S 3 /TiO 2 composite NFs exhibited promising charge separation efficiency and high visible light photocatalytic activity for degradation of methyl orange and reduction of Cr (VI) under visible light illumination due to the formation of the traditional type‐II heterojunction between In 2 S 3 nanosheets and TiO 2 NFs ( Figure a).…”
Section: Electrospun Tio2 Nfsmentioning
confidence: 99%
“…Semiconductor-based photocatalysts have attracted more and more attention, since Fujishima’s team found water splitting with TiO 2 in 1972 [ 1 ]. Especially in recent years, many promising semiconductor photocatalysts, such as TiO 2 [ 2 , 3 , 4 , 5 ], ZnO [ 6 , 7 , 8 ] and SnO 2 [ 9 , 10 , 11 , 12 ], have been widely reported. Among those, graphite-like phase carbon nitride (g-C 3 N 4 ), with inexpensive, physicochemical stability and suitable potentials, has been extensively used to degrade refractory organic contaminants and hydrogen production as new metal-free semiconductor photocatalysts [ 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in recent years, many promising semiconductor photocatalysts, such as TiO 2 [ 2 , 3 , 4 , 5 ], ZnO [ 6 , 7 , 8 ] and SnO 2 [ 9 , 10 , 11 , 12 ], have been widely reported. Among those, graphite-like phase carbon nitride (g-C 3 N 4 ), with inexpensive, physicochemical stability and suitable potentials, has been extensively used to degrade refractory organic contaminants and hydrogen production as new metal-free semiconductor photocatalysts [ 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. However, the low sunlight response caused by its intrinsic band gap (2.7 eV), and the strong recombination rate and low mobility of charge carrier have restricted the photocatalytic activity of single g-C 3 N 4 [ 16 , 17 , 18 ] seriously.…”
Section: Introductionmentioning
confidence: 99%
“…When a material is subjected to external perturbation, e.g., an electron beam or femtosecond (fs) pulse laser irradiation, a large amount of energy is interchanged through nonequilibrium processes, thereby altering the geometry, electronic structure, and morphology of the irradiated material. [4][5][6][7] These changes cause unexpected effects on their physical and chemical properties, e.g., photoluminescence emission, 8 photodegradation, 9 antimicrobial activity, 10 and the growth of nanostructures. 10,11 Excellent studies have been published on electron beaminduced syntheses 12,13 and how different functional nanomaterials and nanostructures have been successfully fabricated using fs laser treatment for several practical applications.…”
Section: Introductionmentioning
confidence: 99%